2021
DOI: 10.1007/s10570-021-04205-x
|View full text |Cite
|
Sign up to set email alerts
|

Micro/nanostructured lignonanocellulose obtained from steam-exploded sugarcane bagasse

Abstract: This work demonstrates the isolation of lignocellulose micro-nanofibrils, nanocrystals and nanospheres from steam-exploded sugarcane bagasse (SEB). First, steam-explosion was carried out in sugarcane bagasse at 195 °C for 7.5 and 15 min (SEB-7.5 and SEB-15). Untreated sugarcane bagasse was also pretreated by mechanical refining (MRB) in a PFI mill for comparison. Then, SEB and MRB fibers were submitted to alkaline delignification, hypochlorite bleaching for 60 or 180 min (HB60 and HB180), enzymatic hydrolysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 76 publications
1
5
0
Order By: Relevance
“…They may correspond to lignin released from the fiber surface during HPH treatment in the form of nanoparticles or correspond to the precipitation of dissolved lignin after the MA treatment at a temperature exceeding 100 °C. The presence of such spherical particles at the surface of the fibrils has been previously observed by other authors, and the effect of HPH over the lignin content during fibrillation has been reported to decrease. ,, The lignin nanoparticles (NPs) appeared to be well distributed within the nanocellulose networks. It is worth mentioning that a fraction of free lignin NPs was also present in the supernatant recovered by filtration of the HTT-treated biomass (Figure S3).…”
Section: Resultssupporting
confidence: 52%
See 2 more Smart Citations
“…They may correspond to lignin released from the fiber surface during HPH treatment in the form of nanoparticles or correspond to the precipitation of dissolved lignin after the MA treatment at a temperature exceeding 100 °C. The presence of such spherical particles at the surface of the fibrils has been previously observed by other authors, and the effect of HPH over the lignin content during fibrillation has been reported to decrease. ,, The lignin nanoparticles (NPs) appeared to be well distributed within the nanocellulose networks. It is worth mentioning that a fraction of free lignin NPs was also present in the supernatant recovered by filtration of the HTT-treated biomass (Figure S3).…”
Section: Resultssupporting
confidence: 52%
“…Indeed, other HTT treatments, such as steam explosion (SE), have been reported to successfully solubilize and depolymerize hemicellulose, while having a milder effect over cellulose and lignin. 40 , 41 In addition, the more severe effect over hemicellulose and lignin fractions due to the presence of MA has been also reported, particularly for MA concentrations exceeding 50 wt % and high temperatures. 42 Considering the main objective of the present work, i.e., preserving the lignin content as much as possible during the conversion of DPW into LCNFs, the highest temperature of the experimental batch was set at 150 °C and the MA concentration at a maximum of 30 wt %.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Need specific equipment [43,44] Cryocrushing Extreme temperature reduction is conducted to embrittle the interior of the fiber, and then fiber fibrillation is realized Improve heat stability High cost for equipment [24,39]…”
Section: Less Use Of Chemical Reagents High Efficiencymentioning
confidence: 99%
“…Both pretreatments have been reported to have a minor effect on the chemical composition of the neat fibers, which clearly indicates that most of the initial resource is preserved. Nonetheless, while it is true that the presence of lignin and other amorphous constituents promote fibrillation during high-pressure homogenization, for instance, it is also worth noting that other nanostructured particles may be released, like lignin nanoparticles [ 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%